Ojcostwo - kryzys czy nowy wymiar? - Michałowska, Elżbieta; Daniłowicz, Paweł (Wydawnictwo Naukowe UAM, 2011)
Between 2008 and 2009 research was conducted on childrens' and youths' sense of security at home and at school. The research covered 18 000 schoolchildren from Łódź. The main goal was to determine main family, school and environmental factors which have influence on violence behaviors increase. Additionally the results revealed dramatic situation of family in Łódź and particularly degreasing meaning of father and fatherhood. The analysis of fatherhood problems was applied to more general theoretical context - crisis of masculinity. Next part of paper is dedicated to fatherhood crisis understood not only as fathers' absence or devaluation of general fathers' position in family but also as underestimation of fathers' presence. Fathers' image becomes unclear, blurred, and his responsibility becomes limited. Also results of this process, that are mentioned in literature, were pointed out. In the empirical part consequences of fathers' absence (both physical and mental) were discussed based on quantity and focus research. Those results allowed to form significant conclusions on "maternalisation" of Łódź family and on childrens' behavior (children raised by fathers tend to transgress certain social normatives).
Fatherhood, crisis, or new dimension?
Keywords: Ojcostwo; Fatherhood; Kryzys; Crisis